Improving the efficiency of the apparatus with counter swirling flows for the food industry - Савченко-Перерва, Марина Юріївна; Якуба, Олександр Родіонович (Eastern-European Journal of Enterprise Technologies, 2015)
The tendency for increased process performance, reduced sizes of plants, accelerated processes occurring in them led to the broader study of dust separation equipment concerning the mathematical modeling of the dust particle separation process in the system of counter swirling flows (CSF) as well as the areas of their structural improvement. To eliminate the inhibitory effect of angular momentum in the primary swirler and align relationships with gas flow rates, the angular momentum equation for the new ACSF (apparatus with counter swirling flows), which allowed to find a place for structural improvement was derived. The dependencies of velocity fields of gas flows and overall efficiency of the apparatus with counter swirling flows before and after the improvement using previously obtained methods for calculating the flow patterns were proposed. The methodology for calculating fractional efficiency for each layer in the apparatus: external, internal and overall effectiveness was developed. The Walter Bart method for calculating the resistance of an experimental model of the apparatus with counter swirling flows was used. Based on the research, summarized and optimal calculations for finding ACSF pressure losses since it is one of the main characteristics in the energy efficiency evaluation were proposed.